(untitled) (Global Journal of Human-Social Science, 2021)
This paper examines sexism and gender representations in the Kenyan electronic media. It focuses on how gender inequalities and social stereotypes are challenged in a media context by critically analysing the linguistic choices used in Kenyan popular radio programmes to describe women and men. Anchored on critical discourse analysis, the paper analyses linguistic choices from Classic 105 Morning Show hosted by Maina Kageni and Daniel Ndambuki (Mwalimu King’ang’i). Focus is on metaphors, adjectives and nominals that have been purposively selected and which are used to describe men and women in different ways. These are critically scrutinized using Fairclough’s (2010) Textually Oriented Discourse Analysis procedure, together with Sunderland’s (2004) Gendered Discourse approach; these are key in revealing how language is used to break ideological assumptions which have been taken to be commonsensical; expected and even good, and which contribute to changing existing unequal power relations. The argument foregrounded in this paper is that relentless sexism, particularly in its subtle form, drives people-women-away from being ambitious and achieving their potential in business, politics and other social spheres hence it needs to be uncovered, discussed and challenged -this has been achieved.